Proceedings of the Third Symposium on Information Interaction in Context 2010
DOI: 10.1145/1840784.1840812
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in gaze patterns for web search

Abstract: We investigate how people interact with Web search engine result pages using eye-tracking, to provide a detailed understanding of the patterns of user attention. Previous research has examined the visual attention devoted to the 10 organic search results, and we extend this by also examining how gaze is distributed across other components of contemporary search engines, such as ads and related searches.This provides insights about searcher's interactions with the -whole page‖, and not just individual component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 24 publications
5
64
0
4
Order By: Relevance
“…Aula et al [3] identified two general patterns that people used in examining search results: exhaustive evaluators (54% of the participants who looked at more than half of the visible results for more than half the tasks) and economic evaluators (46% of the participants). Dumais et al [12] performed a similar analysis of search behavior using more complex result pages that included both organic results and advertisements. They found three general groups of searchers -exhaustive (32%), economic with a focus on results (39%), and economic with a focus on advertisements (29%).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Aula et al [3] identified two general patterns that people used in examining search results: exhaustive evaluators (54% of the participants who looked at more than half of the visible results for more than half the tasks) and economic evaluators (46% of the participants). Dumais et al [12] performed a similar analysis of search behavior using more complex result pages that included both organic results and advertisements. They found three general groups of searchers -exhaustive (32%), economic with a focus on results (39%), and economic with a focus on advertisements (29%).…”
Section: Related Workmentioning
confidence: 99%
“…However these studies are typically conducted in laboratories using a small number of participants with assigned tasks (e.g., [9][15]), with summaries of gaze behavior aggregated across participants and tasks. Some studies examined individual and task differences in gaze patterns, and found individual differences in the strategies with which users inspect results [12], and different clusters of users who exhibit similar result examination behaviors [3] [12]. Others found that the type of search task (informational vs. navigational) influenced task completion time and time spent reviewing documents [9] [27].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the user behavior in the Smucker and Jethani study is representative of actual result list processing behavior given the similarity between the study's observed behavior and that reported by other researchers (cf. strategies in Aula [1] and Dumais et al [9], probabilities of clicking on summaries in Yilmaz et al [31]). …”
Section: Calibration Of Model Componentsmentioning
confidence: 99%
“…Buscher et al [2010] show that the amount of visual attention users spend on different parts of a web page depends on the task type and the quality of the information provided. Dumais et al [2010] show that these "gaze patterns" differ significantly from user to user, suggesting that different UIs may be optimal for different groups of users. In a study of the cognitive costs associated with decision making, Chabris et al [2009] show that users allocate time for a decision-making task according to cost-benefit principles.…”
Section: Related Workmentioning
confidence: 97%